2014
DOI: 10.1016/j.powtec.2014.01.085
|View full text |Cite
|
Sign up to set email alerts
|

Measuring attrition resistance of oxygen carrier particles for chemical looping combustion with a customized jet cup

Abstract: A customized jet cup for measuring attrition resistance of oxygen carrier particles for chemical looping combustion has been constructed and used to evaluate 25 different material samples, all of which previously have been subject to continuous operation in chemical looping reactors at Chalmers University of Technology. The effect of continuous operation has been assessed by comparing attrition behaviour of fresh particles with that of used ones. It is concluded that the correlation between the jet cup tests a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 151 publications
(97 citation statements)
references
References 51 publications
3
94
0
Order By: Relevance
“…to improve this factor. Nevertheless, particles with a crushing strength value lower than 1 N could be selected for the following test, but it must be taken into account that there will be a high risk of particle integrity failure [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to improve this factor. Nevertheless, particles with a crushing strength value lower than 1 N could be selected for the following test, but it must be taken into account that there will be a high risk of particle integrity failure [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, the results were not definitive in many cases. As an example, Rydén et al [9] found that many materials exhibited a poor correlation between their attrition behaviour in continuous CLC units and their corresponding crushing strength values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported attrition index was calculated from measurements using a customized jet cup; see the article by Rydén et al for a description of the jet cup and methodology [32]. The results from these tests with fresh material are used here as a comparison to the experimental attrition behavior in the hot unit.…”
Section: Oxygen Carrier Materialsmentioning
confidence: 97%
“…al. for a description of the jet cup and methodology [27]. This method has been suggested and used as an alternative to the ASTM D5757-95 method.…”
Section: Combined Iron-manganese-silica Oxygen Carriersmentioning
confidence: 99%